Primary malignant giant cell tumor of the sternum - Mohammed Imaduddin; Pavithra Ayyanar; Mahesh Sultania; Dillip Muduly; Mukund Namdev Sable; Suprava Naik; Sambit Mohanty; Madhabananda Kar (University of São Paulo, 2021)
Primary malignant giant cell tumor (PMGCT) is a diagnosis based on the presence of a high-grade sarcomatous component along with a typical benign giant cell tumor (GCT). We report the first case of PMGCT of the sternum in a 28-year-old male with painless swelling over the manubrium sterni. The differential diagnoses of PMGCT and giant cell-rich osteosarcoma were considered. Surgical resection was performed, and the reconstruction was done with a neosternum using polymethyl methacrylate and prolene mesh. At 30 months follow-up, the patient is disease-free.